Lateral Flagellar Gene System of Vibrio parahaemolyticus - Stewart, Bonnie J. (American Society for Microbiology, 2003)
Vibrio parahaemolyticus possesses dual flagellar systems adapted for movement under different circumstances. A single polar flagellum propels the bacterium in liquid (i.e., swimming) with a motor that is powered by the sodium motive force. Multiple proton-driven lateral flagella enable translocation over surfaces (i.e., swarming). The polar flagellum is produced continuously, while production of lateral flagella is induced when the organism is grown on surfaces. This work describes the isolation of mutants with insertions in the structural and regulatory laf genes. A Tn5-based lux transcriptional reporter transposon was constructed and used for mutagenesis and subsequent transcriptional analysis of the laf regulon. Twenty-nine independent insertions were distributed within 16 laf genes. DNA sequence analysis identified 38 laf genes in two loci. Among the mutants isolated, 11 contained surface-induced lux fusions. A hierarchy of laf gene expression was established following characterization of the laf::lux transcriptional fusion strains and by mutational and primer extension analyses of the laf regulon. The laf system is like many enteric systems in that it is a proton-driven, peritrichous flagellar system; however, laf regulation was different from the Salmonella-Escherichia coli paradigm. There is no apparent flhDC counterpart that encodes master regulators known to control flagellar biosynthesis and swarming in many enteric bacteria. A potential σ(54)-dependent regulator, LafK, was demonstrated to control expression of early genes, and a lateral-specific σ(28) factor controls late flagellar gene expression. Another notable feature was the discovery of a gene encoding a MotY-like product, which previously had been associated only with the architecture of sodium-type polar flagellar motors.